Modeling the civil servant discipline in Indonesia: partial least square-structural equation modeling approach - Soelaiman, Nur Fauzi; Ahmad, Sharifah Sakinah Syed; Mohd, Othman; Al Hakim, Rosyid Ridlo; Hidayah, Hexa Apriliana (Asean International Journal of Business, 2022)
Purpose – This paper seeks to discover the factors that influence the supervisor to give the punishment level to civil servant staff—the data being used is a questionnaire to several civil servants in public academic institutions. Methodology/approach – This research used computational tools to classify transgressions into punishment categories (light, medium, or severe) with the model using the data science technique based on the partial least square-structural equation modeling (PLS-SEM) approach. Findings – It was found that the model of civil servant discipline in Indonesia is based on 14 hypotheses from bootstrapping technique and by using data science technique to support the result analysis of PLS-SEM. Novelty/value – This research contributed to providing civil servant supervisors to understand factors that influence the discipline of their staff, so it can be used to determine the punishment categorization.